MANAGEMENT OF PASTURE BLOAT IN A POST-PARTURIENT WEST (2020)
"A two and half year old post parturient West African Dwarf ewe, weighing 22 kgs and with black anterior and white posterior body coat was presented at the Veterinary Teaching Hospital, University of Ibadan, with complaints of abdominal distension, sudden laboured breathing and anorexia. The animal was said to have lambed 7 days earlier and was fed with cassava peels and grasses. On clinical examination, the eye ball appeared bulged and starry; the stomach was hard on palpation with frothy buccal exudate and persistent grinding of teeth. The heart rate was 68/minute, respiratory rate was 15/minute and rectal temperature was 39.8oC. Bloat was clinically diagnosed. With the patient properly restrained, an improvised stomach tube was rinsed in vegetable oil and slowly inserted through the oesophagus into the rumen and the gas eructated. Liquid paraffin (15 mls) was subsequently introduced into the rumen via the tube. On removing the stomach tube, a long strand of fresh undigested pasture came out with the tube from the gastrointestinal tract. The hard stomach was thereafter relieved within 5 minutes of the procedure. Long acting Oxytetracycline hydrochloride (2 mls) and 1ml Diclofenac were administered (intramuscularly) simultaneously at different injection sites. Plenty of water was advised to be given orally after 30minutes. Complication resolved and complete recovery of the ewe was achieved after 5 consecutive days of treatment.